Gender differences in entrepreneurial choice and risk aversion: a decomposition based on a microeconometric model - Frank M. Fossen (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Why are female entrepreneurs so rare? Women have both to a lower entry rate into selfemployment and a higher exit rate in Germany. To explain the gender gap, a structural microeconometric model of the transition rates is estimated, which includes a standard risk aversion parameter. As inputs into the model, the expected value and variance of earnings from self-employment and dependent employment are estimated separately by gender, accounting for non-random selection into the employment states. The gender differential in the transition rates is decomposed using a novel extension of the Blinder-Oaxaca technique for nonlinear models. Women's higher estimated risk aversion is found to explain the largest part of their higher exit rate, but only a small part of their lower entry rate.
Keywords: J23; J16; D81; 330; Entrepreneurship; self-employment; risk aversion; gender differential; nonlinear Blinder-Oaxaca decomposition; Unternehmer; Selbstständige; Weibliche Führungskräfte; Risikoaversion; Geschlecht; Dekompositionsverfahren; Schätzung; Deutschland